2022
DOI: 10.7759/cureus.25361
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Duct Hamartomas: A Systematic Review

Abstract: Biliary duct hamartomas are benign intrahepatic bile duct lesions. Despite being primarily incidental findings on imaging, these lesions can provide a diagnostic conundrum due to their shared characteristics with malignant tumors. The goal of this systematic review is to offer a thorough clinical profile of biliary duct hamartomas. There were 139 cases of biliary duct hamartomas identified in a structured systematic review of the literature. Patient demographics, clinical presentation, significant l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 87 publications
1
8
0
Order By: Relevance
“…Several studies have found that the lesions, specifically the septae, become more distinct, rather than contrast enhancing on CT (Eisenberg et al, 1986;Ryu et al, 2010;Sheikh et al, 2022). This is a perplexing characteristic that could result in a malignancy diagnosis in humans (Sheikh et al, 2022). In the present case report, the differential diagnoses changed depending on the imaging modality used.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Several studies have found that the lesions, specifically the septae, become more distinct, rather than contrast enhancing on CT (Eisenberg et al, 1986;Ryu et al, 2010;Sheikh et al, 2022). This is a perplexing characteristic that could result in a malignancy diagnosis in humans (Sheikh et al, 2022). In the present case report, the differential diagnoses changed depending on the imaging modality used.…”
Section: Discussionmentioning
confidence: 62%
“…Rarely, cases can present with nonspecific clinical signs, such as pain on abdominal palpation, jaundice or fever. Although the majority of patients have normal laboratory results, some may develop minor haematologic abnormalities, most frequently increased liver enzymes (Carmona et al, 2022;Lanser & Puckett, 2023;Priadko et al, 2022;Sheikh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations